FAKTOR PENDORONG PERILAKU PENGELOLAAN KEUANGAN PADA PELAKU USAHA KECIL DAN MENENGAH - Negina Kencono Putri; Novi Dirgantari (Universitas Budi Luhur, 2022)
This study aims to analyze the influence of the driving factors of financial management behavior in the form of financial knowledge, financial attitudes, and spiritual intelligence on the behavior of SMEs in conducting financial management. This type of research is survey research with a quantitative approach. The sampling technique of 106 SMEs in this study used a convenience random sampling technique. The data used are primary data obtained through a questionnaire. Analysis of the data in the study using multiple regression analysis statistics. The results of this study indicate that financial attitude and financial knowledge of SME actors has a positive effect on financial management behavior. Likewise, spiritual intelligence also has a significant effect on the behavior of SMEs in conducting financial management.